Hormesis and Epidermal Stem Cells - Edward J. Calabrese; Vittorio Calabrese (SAGE Publishing, 2022)
This paper provides an assessment of hormetic dose responses in epidermal stem cells (EpSCs) in animal models and humans, with emphasis on cell proliferation and differentiation and application to wound healing and aging processes. Hormetic dose responses were induced by several agents, including dietary supplements (eg, luteolin, quercetin), pharmaceuticals (eg, nitric oxide), endogenous agents (eg, growth/differentiation factor 5), and via diverse chemical means to sustain steaminess features to retard aging and disease onset. While hormetic dose responses have been extensively reported in a broad spectrum of stem cells, this area has only been explored to a limited extent in EpSCs, principally within the past 5 years. Nonetheless, these findings provide the first integrated assessment of hormesis and EpSC biology within the context of enhancing key functions such as cell proliferation and differentiation and resilience to inflammatory stresses. This paper assesses putative mechanisms of hormetic responses in EpSCs and potential therapeutic applications to prevent dermatological injury and disease.